Immunization History of Children with Inflammatory Bowel Disease - Ing Shian Soon; Jennifer CC deBruy; Iwona Wrobel (Canadian Journal of Gastroenterology)
BACKGROUND: Protection against vaccine-preventable diseases is important in children with inflammatory bowel disease (IBD) due to frequent immunosuppressive therapy use. The chronic relapsing nature and treatment regimen of IBD may necessitate modified timing of immunizations.